INTEREST OF UNIVERSITY STUDENTS IN SURABAYA VETERAN NATIONAL DEVELOPMENT IN FUTSAL FOLLOWING - januar, mardahera raka anugrah; Pramono, Made (Jurnal Kesehatan Olahraga, 2019)
Abstract This study alms to find out the interest of female students at the Surabaya National Veterans Development University in participating in UKM Futsal.This research is quantitative descriptive. Descriptive research method is research conducted to describe certain symptoms, phenomena or events. Quantitative research is data in the form of numbers or qualitative data that is assumed. Technique of data analysis use manual countingThe population in the study were female students of the Surabaya National Veterans Development University who participated in UKM Futsal. Results obtained in this study are in accordance with the procedure. This study uses a questionnaire to retrieve data from respondents to answer the formulation of the problem. This research was carried out at the Futsal Student Activity Unit of the Surabaya Veterans National Development University. Questionnaire in this study consists of 29 statements that are distinguished based on predetermined indicators, which include indicators of motivation, attitudes towards futsal SMEs, families, facilities on campus, social partners, and emotional factors. This questionnaire consists of five alternative answer choices that use a Likert scale to measure interest levels. then tht the interest of female students of the National Development University of Veterans Surabaya in participating in futsal UKM, included in the very high category (82.15%). Keywords: Interest, futsal, student, interest factor.